CALEDONIAN SCOTS PINE ORIGINS AND GENETIC STRUCTURE - Kinloch, Bohun B (The New phytologist, 1986)
Monoterpene and isozyme loci, used as markers to study the genetic structure of Scots pine (Pinus sylvestris L.) native to Scotland, showed that the endemic populations are not genetically impoverished, in spite of severe contraction in range and numbers as a result of both natural and anthropogenic causes. On the contrary, variability in the relict populations is almost the highest: of any plant species studied, with average heterozygosities of 0.33 for monoterpenes (rive loci) and 0.30 for isozymes (16 loci). The overwhelming proportion of this variability (> 95 %) was within populations, even though significant differences in gene frequencies of many individual loci existed among populations. Multiple-locus comparison of gene frequencies among populations, resolved by canonical variate analysis, showed no coherent geographic pattern of differences from population to population or region to region, with one major exception: certain populations in northwestern Scotland (Wester Ross) were distinct from all others and each other. The pattern of variability of the biochemical markers was consistent with that of metrical and physiological traits reported in the literature. These traits, in turn, show relatively little genetic affinity between contemporary Scottish and continental European populations. The genetic evidence, together with the anomalous distribution of pine pollen in the British Isles during the Holocene, suggests that the Caledonian race of Scots pine originated endemically from more than one refugium after the last glaciation